ANALISIS PENGARUH NET OPERATING MARGIN, NON-PERFORMING FINANCING, CAPITAL ADEQUACY RATIO DAN KUALITAS AKTIVA PRODUKTIF TERHADAP PROFITABILITAS BANK UMUM SYARIAH - Rahma Agis Fabiolla; Yenny Kornitasari (Islamic Economics and finance in Focus, 2024)
The role of banks in generating profits has a high impact on the growth and development of sharia inclusion. The low profitability of Islamic banks compared to conventional banks indicates that the bank’s performance is poor. This study aims to analyze the influence of Net Operating Margin (NOM), Non Performing Finance (NPF), Capital Adequacy Ratio (CAR), and Productive Asset Quality affect on the profitability of Islamic banks in Indonesia (ROA). Using secondary time series data from OJK financial reports for January 2018 to April 2023, researchers used multiple linear regression analysis with SPSS24 software. Results indicate that NOM and NPF have a partially positive impact on ROA, while CAR and KAP shows no significant partial effect.   Kata kunci: Profitabilitas; Bank umum syariah; ROA; NOM; NPF; CAR; KAP